أثر التسويق الإلكتروني على تنافسية المؤسسات الخدماتية - عباسة, رافع (My University, 2024)
This study dealt with the impact of e-marketing on the competitiveness of service enterprises from knowing the impact of e-marketing and their competitive performance. In response to this problem, we conducted a study on a sample of Algiers Telecommunications Foundation workers based on the analytical descriptive approach and using statistical methods in the SPSS programme to present and analyse the results of the study. From this field study, it was found that electronic marketing has a critical impact on the competitiveness of service enterprises by strengthening and enhancing their competitive performance in the labor market.
دراسة حالة مؤسسة اتصالات الجزائر -وكالة عين تادلس
Keywords: electronic marketing, modern technology, competitiveness, competitive performance.